Algorithm and software implementation of real-time collaborative editing of graphical schemes using Socket.IO library - Alpatov, Aleksey Nikolaevich; Iurov, Ilia Igorevich (Программные системы и вычислительные методы, 2024)
In the modern world, teamwork is becoming more and more common. Different participants may be in different places, but they still need to work together on the same project, including graphic diagrams. An important aspect of this approach is the ability to observe changes made by other participants in real time. This allows, first of all, to reduce the frequency of conflicts when simultaneously editing the same schema element. However, existing solutions for sharing data in real-time collaborative editing of graphical diagrams face a number of problems, such as delays in data transmission. The subject of research in this article is the development of a minimum viable web application that allows users to perform collaborative graphical editing of a canvas in real time. The object of the study is a model of the process of collaborative editing in real time, taking into account the resolution of emerging conflicts. The research methodology is based on a theoretical approach to identifying mathematical formulas that describe changes in the state of a document when it is jointly edited by users. The characteristics of the use of the HTTP and WebSocket protocols in multi-user client-server applications are given. To use the WebSocket protocol, the Socket.IO library is used. The application server is built using the Express framework. The authors' main contribution to the topic is a model of the real-time collaborative editing process, as well as a mechanism for detecting conflicts for any number of users and a conflict resolution function for each pair of conflicting changes when online collaborative editing of documents. Within the framework of this study, an algorithm for collaborative editing of graphic schemes in real time is additionally proposed and its implementation in the form of a software system is given. The algorithm proposed as a result of the study in the JavaScript programming language can be used as a basis for developing more rich web applications using the Socket.IO library and be the object of future research affecting multi-user interaction and real-time conflict resolution.